Investigation of the Self-efficacy Beliefs in Teaching Science and Attitudes towards Teaching Profession of the Candidate Teachers - Uyanık, Gökhan (Horizon Research Publishing Co., Ltd., 2016)
The aim of this study is to investigate the attitudes of the primary school teacher candidates towards teaching profession and self-efficacy beliefs in teaching science. The research was conducted with a survey model. The sample of the study consisted of 182 teacher candidates who were studying at the 2015-2016 spring term from Kastamonu University, at Faculty of Education in Elementary Teacher Training program at the first and fourth years of university level. Scale of Self-Efficacy Beliefs towards Science Teaching and Scale of Attitudes towards to Teaching Profession were used as data gathering tools. Independent t-testing and Pearson's Correlation Coefficients have been used in analyzing the data. According to findings, there was a significant difference between the freshman and senior students on the self-efficacy scaling related to teaching the science in favor of the senior students. In addition, it was also been discovered that there was also statistical difference in favor of the senior students compared to the freshman students on attitude scale towards to the teaching profession. It has also found that there was a statistical intermediate positive relationship between the self-efficacy of teaching the science and the attitudes towards teaching profession at the teacher candidates, who were studying at the first year of the university. However, it was discovered that there was a higher probability positive relationship between the self-efficacy beliefs and the attitudes to the teaching profession of teacher candidates, who were at the last year of the university.
Keywords: 4. Education